Spiritualitas Kepemimpinan Hamba Menurut Bonhoeffer dan Relevansinya Bagi Pelayanan Pendeta - Winanda Nebuida (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2026)
This study explores the relevance of Dietrich Bonhoeffer's theological ethics, particularly his concepts of